2021
DOI: 10.20473/tijab.v5.i1.2021.81-93
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Altman, Springate, and Zmijewski Models in Predicting the Bankruptcy of Retail Companies in Indonesia and Singapore

Abstract: This study aims to determine whether there is a difference in the prediction results between the Altman, Springate, and Zmijewski models and the most accurate prediction model for predicting the bankruptcy of retail companies in Indonesia and Singapore. This research is descriptive quantitative. The sampling method used was purposive sampling with 15 Indonesian retail companies and 15 Singapore retail companies. This study used descriptive analysis, normality test, and One Way ANOVA test using an SPSS program.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
(8 reference statements)
1
7
0
6
Order By: Relevance
“…They found that X-score model produced the highest level of prediction accuracy (97.9%). Similar conclusion can be seen in the study of Ashraf et al (2019), Tanjung (2020), Andriani & Sihombing (2021) and Muzanni & Yuliana (2021).…”
Section: Literature Reviewsupporting
confidence: 90%
See 1 more Smart Citation
“…They found that X-score model produced the highest level of prediction accuracy (97.9%). Similar conclusion can be seen in the study of Ashraf et al (2019), Tanjung (2020), Andriani & Sihombing (2021) and Muzanni & Yuliana (2021).…”
Section: Literature Reviewsupporting
confidence: 90%
“…In contrast, having positive X-score (X-score ≥ 0), the firm is then classified into the group with high possibility of financial difficulties. The X-score model (Zmijewski, 1984) has been frequently used to forecast company's financial risks in many countries such as in the US (Sayari & Mugan, 2017;Lagkas & Papadopoulos, 2014), India (Singh & Mishra, 2016), Kuwait (Musaed et al, 2018), Pakistan (Ashraf et al, 2019), Indonesia and Singapore (Nilasari & Haryanto, 2018;Tanjung, 2020;Andriani & Sihombing, 2021;Muzanni & Yuliana, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…If the Z value is below 0.862, then the company is considered to be in danger of bankruptcy. One way to measure the health of a company with the Springate method is to analyze bankruptcy with a sample of 40 companies using the MDA method (Muzanni & Yuliana, 2021). Springate found 4 ratios out of 19 financial ratios that contributed to the prediction of company bankruptcy.…”
Section: Springate Approachmentioning
confidence: 99%
“…Previous research related to the Altman Z-Score bankruptcy prediction model when predicting company bankruptcy produces an accuracy rate of 71.6%-89.5% studied by (Arini, 2021;Mulyani et al, 2018;Muzanni & Yuliana, 2021) Previous research predictive model Springate bankruptcy has an accuracy rate of 60%-83.33% which was studied by (Arini, 2021;Mulyani et al, 2018;Muzanni & Yuliana, 2021). Previous research on the Zmijewski bankruptcy prediction model resulted in an accuracy rate of 60%-87% which was studied by (Mulyani et al, 2018;Muzanni & Yuliana, 2021). Previous research on the Fulmer model in predicting corporate bankruptcy resulted in an accuracy rate of 71.6%-100% (Mulyani et al, 2018;Parquinda & Azizah, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Model Springate (S-Score) namely a bankruptcy prediction method that uses several financial ratios, such as profitability, liquidity, and asset turnover ratios. The Springate model can be used as a method for estimating bankruptcy which has an 80% accuracy rate (Muzanni & Yuliana, 2021). From this description, the following hypothesis is proposed: H2: The financial condition of retail companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2020 period can be measured using the Springate bankruptcy prediction model.…”
Section: Introductionmentioning
confidence: 99%